Walking for fitness make every step count - Barough, Nina (DK Publishing, 2017)
Keep fit, tone-up and lose weight with Try It! Walking for Fitness. Walking is the perfect way to achieve optimum health, hassle free, for all ages and abilities. Power-walking expert Nina Barough reveals there is a world of difference between a casual stroll and an energising, body-sculpting power walk. Founder of the annual Moonwalk, Nina explains how this low-impact form of exercise can be done by anyone, anywhere at anytime and her total walking programme will help you achieve health, vitality and weight-loss. Improve your wellbeing as well as your step count with 12-week walking programmes, as well as plans for warm-up, cool down, stretches, and how to reach your 10,000 steps a day. This book was made for walking